TRANSFORMASI ARSITEKTUR JARINGAN ENTERPRISE MELALUI ADOPSI CLOUD COMPUTING DAN SOFTWARE-DEFINED NETWORKING: TINJAUAN LITERATUR SISTEMATIS - Ridhani, Ahmad Ridhani (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2025)
This research examines enterprise network architecture transformation through cloud computing and Software-Defined Networking implementation using systematic literature review approach. The research methodology applies PICO framework with analysis of 10 high-quality articles from reputable academic databases spanning 2019-2024. Research findings identify that cloud computing and SDN integration creates synergy enabling organizations to achieve significant automation and efficiency levels. Critical success factors for transformation include social influence, facilitating conditions, and effective enterprise architecture implementation. Holistic virtualization and pervasive intelligence become primary enablers in achieving optimal network flexibility. Development prospects demonstrate emerging technology convergence with digital twin paradigm and model-driven techniques as central components of future architecture. This research contributes to understanding enterprise network transformation dynamics and provides comprehensive implementation framework for organizational adoption.